Infection dynamics and disease prevalence of Chlamydia pecorum in koalas across two geographically separated habitats in Southeast Queensland - Chioma M. Ojiako; Peter Timms; Julien Grosmaire; Jessie S.F. Wong; Martina Jelocnik; Nina M. Pollak; Jon Hanger; Deidre de Villiers; Sheri Smit; Samuel Phillips (Veterinary Microbiology, 2026)

The long-term decline of a succulent tree, Aloidendron pillansii, in the hyper-arid Richtersveld region of southern Africa - M. Timm Hoffman; Peter J. Carrick; Michael D. Cramer; Elsabé Swart; Justin J. van Blerk; Helga van der Merwe (Journal of Arid Environments, 2026)

Towards a harmonized database of indoor air contaminant concentrations: Methods and application to CO2 - Gabriel Rojas; Reto Stauffer; Núria Casquero-Modrego; Marcel Loomans; Marc Abadie; Ibrahim Alhindawi; Francesco Babich; Gabriel Bekö; Marie Coggins; Bart Cremers; Bernhard Damberger; Timm Freundorfer; et al. (Building and Environment, 2026)

Soil-erosion events on arable land are nowcast by machine learning - Pedro V.G. Batista; Markus Möller; Karsten Schmidt; Timm Waldau; Kay Seufferheld; Abdelaziz Htitiou; Burkhard Golla; Florian Ebertseder; Karl Auerswald; Peter Fiener (CATENA, 2025)

Pathological findings in raccoon dogs (Nyctereutes procyonoides) in Schleswig-Holstein, Germany - Jana C. Klink; Alexandra Rieger; Peter Wohlsein; Sophie Aurich; Christiane Hoffmann; Christa Ewers; Marie-Kristin Raulf; Christina Strube; Annette Johne; Pavlo Maksimov; Timm Harder; Dennis Rubbenstroth; et al. (Journal of Comparative Pathology, 2025)

Using bioinformatics to investigate functional diversity: a case study of MHC diversity in koalas - Luke W. Silver; Elspeth A. McLennan; Julian Beaman; Karen Burke da Silva; Peter Timms; Carolyn J. Hogg; Katherine Belov (Immunogenetics, 2024)
Conservation genomics can greatly improve conservation outcomes of threatened populations, including those impacted by disease. Understanding diversity within immune gene families, including the major histocompatibility complex (MHC) and toll-like receptors (TLR), is important due to the role they play in disease resilience and susceptibility. With recent advancements in sequencing technologies and bioinformatic tools, the cost of generating high-quality sequence data has significantly decreased and made it possible to investigate diversity across entire gene families in large numbers of individuals compared to investigating only a few genes or a few populations previously. Here, we use the koala as a case study for investigating functional diversity across populations. We utilised previous target enrichment data and 438 whole genomes to firstly, determine the level of sequencing depth required to investigate MHC diversity and, secondly, determine the current level of diversity in MHC genes in koala populations. We determined for low complexity, conserved genes such as TLR genes 10 × sequencing depth is sufficient to reliably genotype more than 90% of variants, whereas for complex genes such as the MHC greater than 20 × and preferably 30 × sequencing depth is required. We used whole genome data to identify 270 biallelic SNPs across 24 MHC genes as well as copy number variation (CNV) within class I and class II genes and conduct supertype analysis. Overall, we have provided a bioinformatic workflow for investigating variation in a complex immune gene family from whole genome sequencing data and determined current levels of diversity within koala MHC genes.

Trees, carbon, and the psychology of landscapes - Lindsey Gillson; M. Timm Hoffman; Peter A. Gell; Anneli Ekblom; William J. Bond (Trends in Ecology & Evolution, 2024)

Effects of drying temperature of corn from the center and extremities of the corncob on drying parameters, protein and starch properties, and carotenoid profile - Newiton da Silva Timm; Paulo Carteri Coradi; Cristiano Dietrich Ferreira; Adriano Hirsch Ramos; Marina Peter Schwab; Maurício de Oliveira (Food Research International, 2023)

Monitoring of Anthropogenic Sediment Plumes in the Clarion-Clipperton Zone, NE Equatorial Pacific Ocean - Sabine Haalboom; Timm Schoening; Peter Urban; Iason-Zois Gazis; Henko de Stigter; Benjamin Gillard; Matthias Baeye; Martina Hollstein; Kaveh Purkiani; Gert-Jan Reichart; Laurenz Thomsen; Matthias Haeckel; et al. (Frontiers in Marine Science, 2022)
The abyssal seafloor in the Clarion-Clipperton Zone (CCZ) in the NE Pacific hosts the largest abundance of polymetallic nodules in the deep sea and is being targeted as an area for potential deep-sea mining. During nodule mining, seafloor sediment will be brought into suspension by mining equipment, resulting in the formation of sediment plumes, which will affect benthic and pelagic life not naturally adapted to any major sediment transport and deposition events. To improve our understanding of sediment plume dispersion and to support the development of plume dispersion models in this specific deep-sea area, we conducted a small-scale, 12-hour disturbance experiment in the German exploration contract area in the CCZ using a chain dredge. Sediment plume dispersion and deposition was monitored using an array of optical and acoustic turbidity sensors and current meters placed on platforms on the seafloor, and by visual inspection of the seafloor before and after dredge deployment. We found that seafloor imagery could be used to qualitatively visualise the redeposited sediment up to a distance of 100 m from the source, and that sensors recording optical and acoustic backscatter are sensitive and adequate tools to monitor the horizontal and vertical dispersion of the generated sediment plume. Optical backscatter signals could be converted into absolute mass concentration of suspended sediment to provide quantitative data on sediment dispersion. Vertical profiles of acoustic backscatter recorded by current profilers provided qualitative insight into the vertical extent of the sediment plume. Our monitoring setup proved to be very useful for the monitoring of this small-scale experiment and can be seen as an exemplary strategy for monitoring studies of future, upscaled mining trials. We recommend that such larger trials include the use of AUVs for repeated seafloor imaging and water column plume mapping (optical and acoustical), as well as the use of in-situ particle size sensors and/or particle cameras to better constrain the effect of suspended particle aggregation on optical and acoustic backscatter signals.

A targeted approach to investigating immune genes of an iconic Australian marsupial - Luke W. Silver; Yuanyuan Cheng; Bonnie L. Quigley; Amy Robbins; Peter Timms; Carolyn J. Hogg; Katherine Belov (Molecular Ecology, 2022)
Disease is a contributing factor to the decline of wildlife populations across the globe. Koalas, iconic yet declining Australian marsupials, are predominantly impacted by two pathogens, Chlamydia and koala retrovirus. Chlamydia is an obligate intracellular bacterium and one of the most widespread sexually transmitted infections in humans worldwide. In koalas, Chlamydia infections can present as asymptomatic or can cause a range of ocular and urogenital disease signs, such as conjunctivitis, cystitis and infertility. In this study, we looked at differences in response to Chlamydia in two northern populations of koalas using a targeted gene sequencing of 1209 immune genes in addition to genome‐wide reduced representation data. We identified two MHC Class I genes associated with Chlamydia disease progression as well as 25 single nucleotide polymorphisms across 17 genes that were associated with resolution of Chlamydia infection. These genes are involved in the innate immune response (TLR5) and defence (TLR5, IFNγ, SERPINE1, STAT2 and STX4). This study deepens our understanding of the role that genetics plays in disease progression in koalas and leads into future work that will use whole genome resequencing of a larger sample set to investigate in greater detail regions identified in this study. Elucidation of the role of host genetics in disease progression and resolution in koalas will directly contribute to better design of Chlamydia vaccines and management of koala populations which have recently been listed as “endangered.”

Phylogenetic and geographical analysis of a retrovirus during the early stages of endogenous adaptation and exogenous spread in a new host - Bonnie L. Quigley; Faye Wedrowicz; Fiona Hogan; Peter Timms (Molecular Ecology, 2021)
Most retroviral endogenization and host adaptation happened in the distant past, with the opportunity to study these processes as they occurred lost to time. An exception exists with the discovery that koala retrovirus (KoRV) has recently begun its endogenization into the koala ( Phascolarctos cinereus ) genome. What makes this opportunity remarkable is the fact that Northern Australian koalas appear to be undergoing endogenization with one KoRV subtype (KoRV‐A), while all subtypes (KoRV‐A‐I) coexist exogenously, and Southern Australian koalas appear to carry all KoRV subtypes as an exogenous virus. To understand the distribution and relationship of all KoRV variants in koalas, the proviral KoRV envelope gene receptor binding domain was assessed across the koala's natural range. Examination of KoRV subtype‐specific proviral copy numbers per cell found that KoRV‐A proviral integration levels were consistent with endogenous incorporation in Northern Australia (southeast Queensland and northeast New South Wales) while revealing lower levels of KoRV‐A proviral integration (suggestive of exogenous incorporation) in southern regions (southeast New South Wales and Victoria). Phylogeographical analysis indicated that several major KoRV‐A variants were distributed uniformly across the country, while non‐KoRV‐A variants appeared to have undergone lineage diversification in geographically distinct regions. Further analysis of the major KoRV‐A variants revealed a distinct shift in variant proportions in southeast New South Wales, suggesting this as the geographical region where KoRV‐A transitions from being predominantly endogenous to exogenous in Australian koalas. Collectively, these findings advance both our understanding of KoRV in koalas and of retroviral endogenization and diversification in general.

High-throughput immunogenetic typing of koalas suggests possible link between MHC alleles and cancers - Bonnie L. Quigley; Galit Tzipori; Karen Nilsson; Peter Timms (Immunogenetics, 2020)
Characterizing the allelic diversity within major histocompatibility complex (MHC) genes is an important way of determining the potential genetic resilience of a population to infectious and ecological pressures. For the koala ( Phascolarctos cinereus ), endemic diseases, anthropogenic factors and climate change are all placing increased pressure on this vulnerable marsupial. To increase the ability of researchers to study MHC genetics in koalas, this study developed and tested a high-throughput immunogenetic profiling methodology for targeting MHC class I UA and UC genes and MHC class II DAB, DBB, DCB and DMB genes in a population of 82 captive koalas. This approach was validated by comparing the determined allelic profiles from 36 koala family units (18 dam-sire-joey units and 18 parent-joey pairs), finding 96% overall congruence within family profiles. Cancers are a significant cause of morbidity in koalas and the risk factors remain undetermined. Our analysis of this captive population revealed several novel MHC alleles, including a potential link between the DBB*03 allele and a risk of developing cancer. This method offers a reliable, high-throughput protocol for expanded study into koala immunogenetics.

We need both natural and energy solutions to stabilize our climate - Bronson W. Griscom; Guy Lomax; Timm Kroeger; Joseph E. Fargione; Justin Adams; Lucy Almond; Deborah Bossio; Susan C. Cook‐Patton; Peter W. Ellis; Christina M. Kennedy; Joseph Kiesecker (Global Change Biology, 2019)

Detection of Chlamydia trachomatis mRNA using digital PCR as a more accurate marker of viable organism - Samuel Phillips; Lenka A. Vodstrcil; Wilhelmina M. Huston; Amba Lawerence; Peter Timms; Marcus Y. Chen; Karen Worthington; Ruthy McIver; Catriona S. Bradshaw; Suzanne M. Garland; Sepehr N. Tabrizi; Jane S. Hocking (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Characterisation of MHC class I genes in the koala - Yuanyuan Cheng; Adam Polkinghorne; Amber Gillett; Elizabeth A. Jones; Denis O’Meally; Peter Timms; Katherine Belov (Immunogenetics, 2018)

Application of Adaptive Starling-Like Controller to Total Artificial Heart Using Dual Rotary Blood Pumps - Boon C. Ng; Peter A. Smith; Frank Nestler; Daniel Timms; William E. Cohn; Einly Lim (Annals of Biomedical Engineering, 2017)

Multisite rTMS for the Treatment of Chronic Tinnitus: Stimulation of the Cortical Tinnitus Network—A Pilot Study - Astrid Lehner; Martin Schecklmann; Timm B. Poeppl; Peter M. Kreuzer; Veronika Vielsmeier; Rainer Rupprecht; Michael Landgrebe; Berthold Langguth (Brain Topography, 2013)

Auditory cortex is implicated in tinnitus distress: a voxel-based morphometry study - Martin Schecklmann; Astrid Lehner; Timm B. Poeppl; Peter M. Kreuzer; Rainer Rupprecht; Julia Rackl; Julia Burger; Elmar Frank; Göran Hajak; Berthold Langguth; Michael Landgrebe (Brain Structure and Function, 2013)

Competitive interactions between grass and succulent shrubs at the ecotone between an arid grassland and succulent shrubland in the Karoo - Ndafuda Shiponeni; Nicky Allsopp; Peter J. Carrick; M. Timm Hoffman (Plant Ecology, 2011)

Effects of strength training with eccentric overload on muscle adaptation in male athletes - Birgit Friedmann-Bette; Timm Bauer; Ralf Kinscherf; Silke Vorwald; Konstanze Klute; Dirk Bischoff; Helmut Müller; Marc-André Weber; Jürgen Metz; Hans-Ulrich Kauczor; Peter Bärtsch; Rudolf Billeter (European Journal of Applied Physiology, 2010)

Biogeography and ecology of Anostraca (Crustacea) in middle Paroo catchment of the Australian arid-zone - Brian V. Timms; Peter R. Sanders (Hydrobiologia, 2002)

Analysis of promoter sequences from Lactobacillus and Lactococcus and their activity in several Lactobacillus species - Andrea McCracken; Mark S. Turner; Phil Giffard; Louise M. Hafner; Peter Timms (Archives of Microbiology, 2000)

Analysis and Conservation Implications of Koala Genetics - William B. Sherwin; Peter Timms; Jonathan Wilcken; Bronwyn Houlden (Conservation Biology, 2000)
Koalas are the only living member of their family and therefore deserve serious conservation consideration. Koalas have low levels of genetic variation within and among populations in the southern part of their range, where they have experienced many relocations and population crashes since European colonization of Australia. The importance of this change in variation is underlined by preliminary indications that levels of genetic variation may affect fitness in koalas. Techniques have been developed to help identify and monitor genetic problems in koalas and to provide the information and tools to make genetic management an integral part of koala conservation. The koala is currently at an appropriate point for conservation intervention: there is clear evidence of decline in some populations, but the existence of other robust populations offers the possibility of a variety of creative solutions to their conservation problems. Managers should aim to maintain this species' current ecological amplitude (the range of environments in which populations are found) and minimize the loss, fragmentation, or decline of populations. There are no data to suggest that any population requires genetic supplementation. The concepts of evolutionarily significant unit ( ESU) and management unit (MU) can be useful in the genetic management of koalas, including monitoring and management regimes. But ESUs and MUs can also be misleading if they are not interpreted carefully in terms of population history and the ultimate goal of management. Translocations should not involve extensive use of stock from a single source, especially those with low genetic variation, and they require careful management to avoid possible problems when individuals encounter novel strains of the pathogen Chlamydia pecorum , because several genetically distinct strains have been found in koalas, some of which may derive from introduced species. Genetic indicators can and must make considerable contributions to koala management, but they require careful interpretation.

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Presence of antibodies reacting with porcine circovirus in sera of humans, mice, and cattle - I. Tischer; L. Bode; J. Apodaca; H. Timm; D. Peters; R. Rasch; S. Pociuli; E. Gerike (Archives of Virology, 1995)